Pengaruh Kualitas Jasa terhadap Kepuasan Pengguna Jasa Kesehatan (Studi pada Pasien Rawat Inap Rumah Sakit Harapan Kita Ambon) - Risambessy, Agusthina (Jurnal Aplikasi Manajemen, 2008)
Health plays important role in human life, so they can do their activities without any trouble. Therefore, human must keep their health and the institution that runs health service also must give priority in their service. There are a lot of institutions who offer health service in Ambon, the private or the government. But there is question then appears like, do they give good quality of health service to their clients/patients? Ambon Harapan Kita Hospital is one of the private hospitals in Ambon was proposed to be the object of the research. The focus of this study was on the quality of the service. This study was used double regreation analysis test with direct F variable, reliability variable, has significant influences toward satis factory variable health user service. The result of t-test toward both variables, guarantee and empathy, did not have significant influence toward satisfactory variable. Reliability variable was, in fact, dominant influenced the satisfactory of the user of health service. These results show that the efforts from the health service institution in Harapan Kita Hospital should be reevaluated on those factors like its quality, empathy, and the reliability. This was very simple and short research so it is impossible to use its data to predict the quality of health service, but at least, it could give pre information to other researchers who want to continue this study by adding other important variables.